Pengetahuan Orangtua dalam Mencegah Diare pada Balita di Puskesmas Sering - Novita Hasiani Simajuntak; Thasya Damanik; Windy Lumbanraja; Angel Purba; Donris Silalahi; Nita Bangun (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Diarrhea is a condition characterized by increased frequency of bowel movements (BAB) of ≥3 times/day with a more liquid consistency. Diarrhea can be caused by infectious or non-infectious agents. Diarrhea can occur acutely, lasting less than 2 weeks, or chronically, lasting more than 2 weeks. The prevalence of diarrhea in toddlers is 12.3% and in infants is 10.6%.3 Based on data from the Medan City Health Office, the incidence of diarrhea in 2023 is estimated to be 66,802 cases across all ages and 32,324 cases in toddlers, with almost half of diarrhea sufferers being children. The Medan City Health Office reported the incidence of diarrhea in toddlers was 2,894 cases and adults 14,112 cases, or approximately 20.5%. Parents are one of the closest people and act as caregivers for children, so they have a crucial role in controlling diarrhea in children, including early management and prevention. Good parental knowledge, attitudes, and behavior regarding the management and prevention of diarrhea can reduce diarrhea morbidity and mortality in children.